Bacterial species associated with interdigital phlegmon outbreaks in Finnish dairy herds - Miia Kontturi; Reijo Junni; Heli Simojoki; Erja Malinen; Eija Seuna; Kirstine Klitgaard; Minna Kujala-Wirth; Timo Soveri; Sinikka Pelkonen (BMC Veterinary Research, 2019)
Abstract Background Severe outbreaks of bovine interdigital phlegmon (IP) have occurred recently in several free stall dairy herds in Finland. We studied the aetiology of IP in such herds, and the association of bacterial species with the various stages of IP and herds of various morbidity of IP. Nineteen free stall dairy herds with IP outbreaks and three control herds were visited and bacteriological samples collected from cows suffering from IP (n = 106), other hoof diseases (n = 58), and control cows (n = 64). The herds were divided into high morbidity (morbidity ≥50%) and moderate morbidity groups (9–33%) based on morbidity during the first two months of the outbreak. Results F. necrophorum subspecies necrophorum was clearly associated with IP in general, and T. pyogenes was associated with the healing stage of IP. Six other major hoof pathogens were detected; Dichelobacter nodosus, Porphyromonas levii, Prevotella melaninogenica, Treponema spp. and Trueperella pyogenes. Most of the samples of acute IP (66.7%) harboured both F. necrophorum and D. nodosus. We found differences between moderate morbidity and high morbidity herds. D. nodosus was more common in IP lesion in high than in moderate morbidity herds. Conclusions Our result confirms that F. necrophorum subspecies necrophorum is the main pathogen in IP, but also T. pyogenes is associated with the healing stage of IP. Our results suggest that D. nodosus may play a role in the severity of the outbreak of IP, but further research is needed to establish other bacteriological factors behind these severe outbreaks.